Teaching Competency of Pre-Service Teachers in Computer Education and Digital Technology for Education Programs, Faculty of Technical Education, Rajamangala University of Technology Thanyaburi - Prammanee, Noppadol; Torsakun, Obuea; Sriboonraung, Boontan (Academic and Research Journal of Liberal Arts (Online), 2025)
This qualitative research collected data through in-depth interviews with pre-service teachers in professional training. The objectives were to: 1) examine the teaching competencies of pre-service teachers majoring in Computer Education and Digital Technology for Education at the Faculty of Technical Education, Rajamangala University of Technology Thanyaburi, and 2) propose instructional strategies aimed at developing pre-service teachers’ teaching skills and fostering 21st-century skills. The research findings revealed that the critical teaching competencies comprise 11 aspects, namely: 1) preparing for learning, 2) articulating learning objectives, 3) reviewing prior content, 4) employing diverse teaching strategies, formats, and methods, 5) activating learners’ prior knowledge, 6) applying theory to practice, 7) incorporating diverse activities into instructional management, 8) providing feedback, 9) summarizing and reviewing content, 10) assessing and evaluating outcomes, and 11) implementing remedial teaching. Furthermore, the research proposed instructional management strategies to develop teaching skills aligned with 21st-century skills, including: 1) effective lesson introduction, 2) applying appropriate teaching strategies, formats, and methods, 3) activating learners’ prior knowledge, 4) integrating theory into practice, 5) designing engaging learning activities, 6) providing constructive feedback, 7) systematically summarizing learning outcomes, 8) evaluating learning outcomes, and 9) leveraging information technology to enhance instruction.